Preparação de derivados da caulerpina e avaliação dos seus efeitos citotóxicos e microbiológicos - Castro, Gisely Maria Freire Abílio de (2017)
Natural products have played an important role as a source of substances directly used as medicinal agents. Among which, marine organisms constitute a potential source of secondary metabolites with diverse therapeutic properties. Nevertheless, despite the great potential the algological resource of the oceans remains little explored by the pharmaceutical industry. The northeastern coast of Brazil has a great diversity of marine species and some of which, such as Caulerpa Lamouroux algae extract, have been reported to have antinociceptive, spasmolytic, antiviral, antimicrobial, insecticidal, and cytotoxic properties. Several pharmacological attributes of Caulerpa spp. are due to the presence of caulerpine, the major component found in this genus. However, isolated molecules may present limitations, including low solubility or chemical instability. Hence, this study aimed to perform structural modifications of the caulerpine molecule, in order to evaluate their antiviral (anti-HSV-1) and antifungal (anti- Candida spp.) properties. Substitution reactions were carried out at the N-indolyl position by mono-and disubstituted alkyl, benzyl, allyl, propargyl and ethyl acetate groups, in addition to conversion to their acid derivatives. A total of 14 analogues were yielded, of which 12 are unpublished in the literature. The analogues were submitted to cytotoxicity analysis and screened for their antiviral activity against HSV-1, both by the tetrazolium method, and antifungal activity against Candida spp., by determining their minimum inhibitory concentrations. Caulerpinic acid and N-ethyl acid showed cytotoxic concentrations (50% of the maximum effect) of 1035.0 μM and 1004.0 μM, respectively, which were significantly (P<0.05) higher than that of caulerpin. A screening was carried out to assess viral inhibition during infection. Only methyl and ethyl N-substituted acids (derivatives 9 e 10) inhibited HSV-1 by 37.39% and 38.35%, respectively, which was significantly greater (p <0.05) than the inhibition caused by caulerpine (15%). As for post-infection antiviral activity, the following analogues showed superior inhibition over caulerpine (0%): esters of caulerpine Nsubstituted by ethyl – derivatives 02 - (28.66%); propargyl -derivatives 04 (28.05%); benzyl – derivatives 05 - (13.87%); and N-ethyl (29.56%) and N-allyl (14.78%) acids of caulerpine (derivatives 10 e 11, respectively). Among the produced analogues, only the mixture of Nmethyl caulerpine – derivatives 01- and N-methyl-O-ethyl caulerpine – derivatives 14 - exhibited antifungal activity, with minimal inhibitory and fungicidal concentrations ranging between 7.8 and 125 μg/mL. In this study, 12 novel caulerpine analogues were produced, of which 7 showed decreased cytotoxicity as compared to the prototype, as well as increased antiviral activity against human herpes virus type 1. Moreover, a mixture of analogues was found to have potent antifungal activity against Candida spp.